MERENTAS JALAN PANJANG PERDAMAIAN: NEGARA & MASYARAKAT DALAM RESOLUSI KONFLIK - Syafuan Rozi (Jurnal Penelitian Politik, 2006)
Horizontal conflicts that occured in Central Sulawesi, Maluku, and North Maluku have caused more than fiv e thousands casualties and more than fiv e hundred thousands IDPs in North Sulawesi. The conflict has segregated the society into separated communities that live base on religion: Islam and Christian. Research on anatomy o f violence in Indonesia has showed a great development since 1990s. The research was only focused on dominant actors and groups. The research seldom included religious leaders, local leader, and youth leader; neither had it involved IDPs as research object. Therefore this research suggests a development o f people economic model that create cooperation between each members o f society. The model itselfcan generatefamily base economic empowerments thatpromote communalization amongand intra-society. Base on that idea.folksfestival been held periodically, with each villages can produce its special craft andproduct. F o lk ’s fe stiva l can act as peacemaker in annihilating reason fo r conflict. Local wisdom such as panas pela, hibualamo need to be introduced arnong generations o f people.